Factors Related to Women Health Literacy in The Coastal Area at Semarang City - Rani Tiyas Budiyanti; Roro Isyawati Permata Ganggi; Murni Murni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Improving women health literacy is crucial. In addition to improving individual health conditions, a mother is also closer to her child in terms of parenting. Nevertheless, there are still various factors that influence the improvement of health literacy, especially in coastal areas. This study aims to determine the health literacy of women in coastal areas and the factors that influence it. This research is quantitative research with a cross-sectional approach. The research was conducted from March to July 2021 with locations in 4 sub-districts in the coastal area at Semarang City, namely Genuk, Tugu, North Semarang, and West Semarang. Respondents in this study were 220 people who were selected using the cluster random sampling technique. Data were obtained through interviews with questionnaires and analyzed by univariate and bivariate tests. Based on the results of the study, most of the respondents (65.5%) had health literacy at a medium level. Several factors that influence health literacy include education (p-value=0.006 ), motivation (p-value=0.0001), resources (p-value=0.0001), and social culture (p-value=0.011). Increasing knowledge and motivation related to health can be done through informal health training and group sharing. In addition, the support of resources from the government and the support of community leaders is also needed to improve health literacy in coastal areas. Abstrak: Peningkatan literasi kesehatan pada wanita merupakan hal yang krusial. Selain untuk meningkatkan kondisi kesehatan individual, seorang ibu juga lebih dekat dengan anak dalam hal pengasuhan. Meskipun demikian, masih terdapat berbagai faktor yang berpengaruh dalam peningkatan literasi kesehatan terutama di daerah pesisir. Penelitian ini bertujuan untuk mengetahui literasi kesehatan pada wanita di daerah pesisir dan faktor yang mempengaruhinya. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Penelitian dilakukan selama bulan Maret hingga Juli 2021 dengan lokasi di 4 Kecamatan daerah pesisir Kota Semarang yaitu Genuk, Tugu, Semarang Utara dan Semarang Barat. Responden dalam penelitian ini sebanyak 220 orang yang dipilih dengan menggunakan teknik cluster random sampling. Data diperoleh melalui wawancara dengan kuesioner dan dianalisis dengan uji univariat serta bivariat. Berdasarkan hasil penelitian sebagian besar responden (65,5%) memiliki literasi kesehatan dengan dengan level menengah. Beberapa faktor yang berpengaruh terhadap literasi kesehatan diantaranya adalah pendidikan (p=0.006 ), motivasi (p=0.0001), sumber daya (p=0.0001), dan kultur sosial (p=0.011). Peningkatan pengetahuan dan motivasi terkait kesehatan dapat dilakukan melalui pelatihan informal  kesehatan  dan grup sharing. Selain itu dukungan sumber daya dari pemerintah dan dukungan tokoh masyarakat juga diperlukan untuk meningkatkan literasi kesehatan di daerah pesisir.